Knowledge, attitude, and belief of health-care workers toward COVID-19 Vaccine at a tertiary care center in India - Ilesh S Kotecha; Disha Alkeshbhai Vasavada; Parveen Kumar; Lubna Mohammed Rafik Nerli; Deepak Sachidanand Tiwari; Dipesh V Parmar (Wolters Kluwer Medknow Publications, 2022)
Introduction: India approved the "Covishield" vaccine for emergency use and began the first vaccination drive from January 16, 2021. As the new coronavirus disease-2019 (COVID-19) vaccine was developed within a short period, public acceptance for this new vaccine remains uncertain. Vaccine hesitancy remains an important challenge in the immunization against COVID-19. The aim of the current study was to assess different hesitancies, attitude, and beliefs about COVID-19 vaccine among health-care workers. Methods: A cross-sectional study was carried out among health-care professionals from 5th to January 15, just before the commencement of the first vaccination drive. All the participants were requested to fill out semi-structured pro forma containing following sections: (1) demographic details and (2) attitude and belief questionnaire. Following this, a lecture of around 45-60 min was conducted by trained professionals comprising of an education module. After the educational session, participants' willingness to take the vaccine was reassessed. Results: Totally, 598 participants participated in the study. Of these, 47% participants were not willing to take the vaccine. Participants with age <35 years, experience <5 years, and working in rural areas have statistically significant unwillingness to take vaccine, on Chi-square test. Getting sick from vaccine, contracting the disease after vaccination, fear of adverse effect, uncertain efficacy, and death due to vaccine are concerns related to vaccination hesitancy. After the educational session, 82% of the participants were willing to take the vaccine. Conclusion: Inadequate knowledge about vaccine contributed significantly to denial for vaccination. Educational program was effective in addressing the concerns of participants about vaccination, improving vaccine usage and hence control of the COVID-19 pandemic.